Characteristic of Cataract Patients from the Opthalmology Department of RSUP Dr. M.Djamil Padang in 2018-2019 - Emery Wynne Emilza (Majalah Kedokteran Andalas, 2023)
Background: Cataract is an eye lens transparency disorder in the form of cloudiness. The purpose of this study was to determine the characteristics of cataract patients in the opthalmology department of RSUP dr. M Djamil Padang Hospital in 2018-2019. Method : This study was a retrospective descriptive study with total sampling and 181 samples were met the criteria. Result: The patients consisted of senile cataract (72.4%), presenile (14.4%), juvenile (11%), and congenital (2.2%). With bilateral (74%), no family history of cataracts (98.8%) and female (56.4%). Obtained risk factors were eye traumas (16%), local eye diseases (7.2%) and metabolic diseases (31.5%). The morphology obtained in congenital and juvenile were totalis (41.2%) and nuclear (35.2%) while in presenile and senile were posterior subcapsular (47.5%) with 81.8% of them were immature. Surgical management was performed with ECCE (97.1%). Conclusion : Most of the characteristics were senile, bilateral, no family history of cataracts and female. The most common risk factor was metabolic disease namely diabetes melitus. In patients with congenital and juvenile cataracts, the totalis and nuclear forms were most commonly found while in presenile and senile cataracts was posterior subcapsular forms with immature level. Surgical management is mostly handled by ECCE.